PEMBARUAN ISLAM DI KALIMANTAN SELATAN PADA AWAL ABAD KE-20 - Rahmadi Rahmadi (Pascasarjana UIN ANTASARI Banjarmasin, 2014)
Islamic Reform in the early of 20th century in South Kalimantan was spread through a number of ways: through the alumni and scholars of the Middle East, inter-island Banjar trader, written media (magazines and books), Islamic organizations, and educational institutions. These reformations changes the map of religious thought in which there are two major camps: kaum muda and kaum tuha. In some cases, those two camps engaged in a polemic thought in a number of religious issues